Micromorphology and chemistry of mite domatia: mutualistic trait convergence and variation across eight sympatric north American species - Rosemary A. E. Glos; Abrianna J. Soule; Abigail Rose Adams; Macy Arnett; Josephine Marie Eckman; Quinn Isabella Hane; Avery Marie Logan; Emma Rose Morterud; Dominick J. Noeker; Christopher A. Talbot; William Ugorji; Elizabeth VanOstran; et al. (Symbiosis, 2026)
Mite domatia — small structures on plant leaves that house mutualistic mites — are widespread across plants yet remain relatively understudied. Here we investigate the chemistry and micromorphology of mite domatia across sympatric species of broadleaf deciduous woody species that have convergently evolved tuft-form mite domatia. Specifically, we test whether domatia display similar micromorphological and chemical properties using metabolomics and scanning electron microscopy across multiple independent sympatric lineages. To identify domatia-specific phenotypes, we also compare tissue within domatia to that of nearby leaf tissue on each of the four domatium-bearing species, and test whether species with domatia exhibit reduced chemical defense relative to species that lack domatia using four additional species that lack prominent domatia as a control. We found that domatium-bearing species had significantly lower total phenolic concentrations and lower total defense compound abundance compared to control species, consistent with an evolutionary trade-off between chemical and mutualistic defense. However, within leaves, domatium tissue chemical defense did not differ from surrounding laminar tissue. In contrast, trichome morphology showed clear convergent modification: domatium trichomes were 24–31% longer than trichomes elsewhere on the leaf, a pattern reversed in control species. Together, our findings shed light on the degree of phenotypic convergence in a widespread, ecologically important trait.

The winds of change? Attitudes toward wind projects and their electoral implications in Texas - Talbot M. Andrews; Carol Atkinson-Palombo; Oksan Bayulgen; Adam Gallaher; Lyle Scruggs (Energy Policy, 2025)

Chironomid assemblages in surface sediments from 182 lakes across New England and Eastern Canada: Development and validation of a new summer temperature transfer function - Thomas Suranyi; Julie Talbot; Donna Francis; Augustin Feussom Tcheumeleu; Pierre Grondin; Damien Rius; Adam A. Ali; Yves Bergeron; Laurent Millet (Quaternary Science Reviews, 2025)

Identification of genetic loci in lettuce mediating quantitative resistance to fungal pathogens - Harry Pink; Adam Talbot; Abi Graceson; Juliane Graham; Gill Higgins; Andrew Taylor; Alison C. Jackson; Maria Truco; Richard Michelmore; Chenyi Yao; Frances Gawthrop; David Pink; et al. (Theoretical and Applied Genetics, 2022)
Key message We demonstrate genetic variation for quantitative resistance against important fungal pathogens in lettuce and its wild relatives, map loci conferring resistance and predict key molecular mechanisms using transcriptome profiling. Abstract Lactuca sativa L. (lettuce) is an important leafy vegetable crop grown and consumed globally. Chemicals are routinely used to control major pathogens, including the causal agents of grey mould ( Botrytis cinerea ) and lettuce drop ( Sclerotinia sclerotiorum ) . With increasing prevalence of pathogen resistance to fungicides and environmental concerns, there is an urgent need to identify sources of genetic resistance to B. cinerea and S. sclerotiorum in lettuce. We demonstrated genetic variation for quantitative resistance to B. cinerea and S. sclerotiorum in a set of 97 diverse lettuce and wild relative accessions, and between the parents of lettuce mapping populations. Transcriptome profiling across multiple lettuce accessions enabled us to identify genes with expression correlated with resistance, predicting the importance of post-transcriptional gene regulation in the lettuce defence response. We identified five genetic loci influencing quantitative resistance in a F 6 mapping population derived from a Lactuca serriola (wild relative) × lettuce cross, which each explained 5–10% of the variation. Differential gene expression analysis between the parent lines, and integration of data on correlation of gene expression and resistance in the diversity set, highlighted potential causal genes underlying the quantitative trait loci.

Lack of sex-biased dispersal promotes fine-scale genetic structure in alpine ungulates - Gretchen H. Roffler; Sandra L. Talbot; Gordon Luikart; George K. Sage; Kristy L. Pilgrim; Layne G. Adams; Michael K. Schwartz (Conservation Genetics, 2014)

Above‐ and below‐ground responses of C 3 –C 4 species mixtures to elevated CO 2 and soil water availability - JUSTIN D. DERNER; HYRUM B. JOHNSON; BRUCE A. KIMBALL; PAUL J. PINTER; H. Wayne POLLEY; CHARLES R. TISCHLER; THOMAS W. BOUTTON; ROBERT L. LAMORTE; GERALD W. WALL; NEIL R. ADAM; STEVEN W. LEAVITT; MICHAEL J. OTTMAN; et al. (Global Change Biology, 2003)
We evaluated the influences of CO 2 [Control, ∼ 370 µ mol mol − 1 ; 200 µ mol mol − 1 above ambient applied by free‐air CO 2 enrichment (FACE)] and soil water (Wet, Dry) on above‐ and below‐ground responses of C 3 (cotton, G ossypium hirsutum ) and C 4 (sorghum, Sorghum bicolor ) plants in monocultures and two density mixtures. In monocultures, CO 2 enrichment increased height, leaf area, above‐ground biomass and reproductive output of cotton, but not sorghum, and was independent of soil water treatment. In mixtures, cotton, but not sorghum, above‐ground biomass and height were generally reduced compared to monocultures, across both CO 2 and soil water treatments. Density did not affect individual plant responses of either cotton or sorghum across the other treatments. Total (cotton + sorghum) leaf area and above‐ground biomass in low‐density mixtures were similar between CO 2 treatments, but increased by 17–21% with FACE in high‐density mixtures, due to a 121% enhancement of cotton leaf area and a 276% increase in biomass under the FACE treatment. Total root biomass in the upper 1.2 m of the soil was not influenced by CO 2 or by soil water in monoculture or mixtures; however, under dry conditions we observed significantly more roots at lower soil depths ( > 45 cm). Sorghum roots comprised 81–85% of the total roots in the low‐density mixture and 58–73% in the high‐density mixture. CO 2 ‐enrichment partly offset negative effects of interspecific competition on cotton in both low‐ and high‐density mixtures by increasing above‐ground biomass, with a greater relative increase in the high‐density mixture. As a consequence, CO 2 ‐enrichment increased total above‐ground yield of the mixture at high density. Individual plant responses to CO 2 enrichment in global change models that evaluate mixed plant communities should be adjusted to incorporate feedbacks for interspecific competition. Future field studies in natural ecosystems should address the role that a CO 2 ‐mediated increase in C 3 growth may have on subsequent vegetation change.

Acclimation response of spring wheat in a free-air CO2 enrichment (FACE) atmosphere with variable soil nitrogen regimes. 2. Net assimilation and stomatal conductance of leaves - Gerard W. Wall; Neal R. Adam; Talbot J. Brooks; Bruce A. Kimball; Paul J. Pinter; Robert L. LaMorte; Floyd J. Adamsen; Douglas J. Hunsaker; Gabrielle Wechsung; Frank Wechsung; Susanne Grossman-Clarke; Steven W. Leavitt; et al. (Photosynthesis Research, 2000)